Lumbar Transforaminal Epidural Steroid Injection in Patients with Lumbar Radicular Pain; Outcome Results of 2-Year Follow-Up - Hashemi, Masoud; Dadkhah, Payman; Taheri, Mehrdad; Ghasemi, Mahshid; Hosseinpour, Ali (Bulletin of emergency & trauma, 2019)
To evaluate the effectiveness of transforaminal lumbar epidural steroid injections (TFESI) in patients with unilateral radiculopathy due to lumbar intervertebral disc protrusion regarding pain intensity, functional disability, current opioid intake and patients' satisfaction. The study is conducted in a pain management center (Tehran, Iran), during 2018. Inclusion criteria were age ≥18 years, radiculopathy for more than 6 months due to imagine-proved lumbar intervertebral disc protrusion and no response to conservative treatments. Exclusion criteria were spinal canal stenosis, lumbar surgery, and inability to communicate in Persian language. During a phone call interview, cases were instructed to rate their pain intensity according to the visual analogue scale (VAS), functional ability, satisfaction according to the patient satisfaction score (PSQ) and report current opioid use and additional injection and/or surgery. Forty-three (89.5%) of the 48 subjects were reachable for study with mean age of 59.14 years and 16 subjects were men (37.2 %). Mean VAS after intervention was 4.67 and before the intervention was 6.91 ( =0.002). Mean functional disability before intervention was 47.23 and after intervention was 37 ( <0.001). Mean patient satisfaction score was 3.07 while 18 cases reported a PSQ level ≥4.  10 cases reported using opioid for analgesia, 23 cases reported receiving additional TFESIs and 11 reported having undergone lumbar surgery. Lumbar Epidural steroid injection is an effective non-surgical treatment option with regard to pain relief and improvement in functional ability with an average patients' satisfaction during 2 years follow up although nearly 25% of patients may need additional injections and half of the patients may finally proceed to surgery.